Investigating destination fascination in destination loyalty: The key role of perceived enjoyment and memorable tourism experiences - Laela, Ela (School of Tourism, Universitas Ciputra Surabaya, 2024)
Destination loyalty is the key to long-term relationships with tourists that directly impact destination success. This study examines the relationship between destination fascination, perceived enjoyment, and memorable tourism experiences in forming destination loyalty. The statistical population in this study is mountain tourists in Indonesia. A sample of 300 tourists who fit the criteria were asked to answer the questionnaire. The method used in this research is a survey using structural equation modeling analysis techniques. The results revealed that destination fascination affects perceived enjoyment. Destination fascination also affects memorable tourism experiences. Perceived enjoyment affects memorable tourism experiences. Perceived enjoyment affects destination loyalty. Memorable tourism experience affects destination loyalty. The results of this study make a theoretical contribution by deepening the understanding of destination loyalty. In addition, this research makes a practical contribution to the tourism industry.